Left Ventricular Remodeling in Non-syndromic Mitral Valve Prolapse: Volume Overload or Concomitant Cardiomyopathy? - Pype, Lobke L.; Bertrand, Philippe B.; Paelinck, Bernard P.; Heidbuchel, Hein; Van Craenenbroeck, Emeline M.; Van De Heyning, Caroline M. (Frontiers in Cardiovascular Medicine, 2022)
Mitral valve prolapse (MVP) is a common valvular disorder that can be associated with mitral regurgitation (MR), heart failure, ventricular arrhythmias and sudden cardiac death. Given the prognostic impact of these conditions, it is important to evaluate not only mitral valve morphology and regurgitation, but also the presence of left ventricular (LV) function and remodeling. To date, several possible hypotheses have been proposed regarding the underlying mechanisms of LV remodeling in the context of non-syndromic MVP, but the exact pathophysiological explanation remains elusive. Overall, volume overload related to severe MR is considered the main cause of LV dilatation in MVP. However, significant LV remodeling has been observed in patients with MVP and no/mild MR, particularly in patients with bileaflet MVP or Barlow’s disease, generating several new hypotheses. Recently, the concept of “prolapse volume” was introduced, adding a significant volume load to the LV on top of the transvalvular MR volume. Another possible hypothesis is the existence of a concomitant cardiomyopathy, supported by the link between MVP and myocardial fibrosis. The origin of this cardiomyopathy could be either genetic, a second hit (e.g., on top of genetic predisposition) and/or frequent ventricular ectopic beats. This review provides an overview of the different mechanisms and remaining questions regarding LV remodeling in non-syndromic MVP. Since technical specifications of imaging modalities impact the evaluation of MR severity and LV remodeling, and therefore might influence clinical decision making in these patients, this review will also discuss assessment of MVP using different imaging modalities.